Innovative thermodynamic parametric investigation of gas and steam bottoming cycles with heat exchanger and heat recovery steam generator: Energy and exergy analysis - M. N. Khan; I. Tlili (Energy Reports, 2018)
In this study, gas and steam bottoming cycles, driven by the exhaust gas of Gas turbine cycle, are analyzed thermodynamically. The waste heat of the Gas turbine topping cycle (GT) exhaust gas is used partially to heat the air in the air bottoming cycle and partially to generate steam by passing it through HRSG in the steam bottoming cycle. The topping Gas turbine and air bottoming cycles are coupled with the heat exchanger, whereas the topping and steam bottoming cycles are coupled with Heat Recovery Steam Generator (HRSG). The effects of turbine inlet temperature (1100 K È TIT È 1500 K), pressure ratio (6ÈrptÈ12) and flow rate of exhaust gas on the Net work and combined thermal efficiency and exergy loss of exhaust gas are investigated. It is observed that the Net work of steam bottoming cycle is higher than the Net work of gas bottoming cycle and for higher values of turbine inlet temperature TIT~=~1500~K, 90% of power is recovered through the bottoming cycle at lower pressure ratio. The combined thermal efficiency increases by 10% with an increase in the turbine inlet temperature from 1100 to 1500~K. It is found that the combined thermal efficiency increases with all pertinent parameters.
Keywords: 330; Efficiency; Energy; Exergy; Bottoming cycles; Heat exchanger; Heat recovery steam generator; Parametric analysis